Hubungan di antara hukuman dengan perubahan sikap: Satu kajian kes di kalangan operator pengeluaran wanita di Sharp Manufacturing Corporation (Malaysia) Sdn. Bhd Batu Pahat, Johor. - Yatim, Zulkifli (2004)

(untitled)
This is a survey research aimed to identify level of understanding among female operators to find difference among respondents’ demographic background (age, marital status, tenure and educational qualification) with respect to the attitude change and to find the relationship between punishment and attitude dimensions which are affective dimension, cognitive dimension and behavioral dimension, among female production operators at Sharp Manufacturing Corp. (M) Sdn Bhd. A total of 59 female production operators who had received punishment participated in this research. Respondents were given questionnaire booklets containing questions that were divided into five sections; demographic background; understanding about punishment; affective dimension; cognitive dimension and behavioral dimension. Score frequency analysis and Spearman’s Correlation Coefficient had been employed to analyze the data. The research findings showed that the respondents’ understanding was at medium level to high level whereby the relationship between punishment and attitude dimensions was weak. There were significant relationships between punishment and cognitive and behavioral dimensions. No significant relationship was found between punishment and affective dimension.